2013
DOI: 10.1289/ehp.1205994
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness and Plasma Asymmetric Dimethylarginine in Mexican Children Exposed to Inorganic Arsenic

Abstract: Background: Arsenic exposure is a risk factor for atherosclerosis in adults, but there is little information on arsenic and early risk biomarkers for atherosclerosis in children. Carotid intima-media thickness (cIMT) is an indicator of subclinical atherosclerotic burden that has been associated with plasma asymmetric dimethylarginine (ADMA), a predictor of cardiovascular disease risk.Objectives: The aim of this study was to investigate associations of arsenic exposure with cIMT, ADMA, and endothelial adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Numerous studies have assessed subclinical and intermediate cardiovascular endpoints that are surrogate endpoints commonly utilized in cardiovascular research, such as blood pressure/ hypertension (e.g., Guha Mazumder et al, 2012;Islam et al, 2012;Kim and Lee 2011;Jones et al, 2011;Chen et al, 2007;Kwok et al, 2007), QT prolongation (the QT interval on a surface electrocardiogram represents the depolarization and subsequent repolarization of the heart's ventricles, and as the interval lengthens, an individual is at greater risk for ventricular tachyarrhythmias) and other arrhythmic changes (e.g., Wang et al, 2009;Mordukhovich et al, 2009;Yildiz et al, 2008;Chen et al, 2007a), and intima media thickness (iMT) (e.g., Wang et al, 2009;Chen et al, 2006Chen et al, , 2013cOsorio-Yáñez et al, 2013). For each of the aforementioned changes, results are inconsistent, even at moderate to high exposure levels.…”
Section: Epidemiology Of Inorganic Arsenic and Cvdmentioning
confidence: 99%
“…Numerous studies have assessed subclinical and intermediate cardiovascular endpoints that are surrogate endpoints commonly utilized in cardiovascular research, such as blood pressure/ hypertension (e.g., Guha Mazumder et al, 2012;Islam et al, 2012;Kim and Lee 2011;Jones et al, 2011;Chen et al, 2007;Kwok et al, 2007), QT prolongation (the QT interval on a surface electrocardiogram represents the depolarization and subsequent repolarization of the heart's ventricles, and as the interval lengthens, an individual is at greater risk for ventricular tachyarrhythmias) and other arrhythmic changes (e.g., Wang et al, 2009;Mordukhovich et al, 2009;Yildiz et al, 2008;Chen et al, 2007a), and intima media thickness (iMT) (e.g., Wang et al, 2009;Chen et al, 2006Chen et al, , 2013cOsorio-Yáñez et al, 2013). For each of the aforementioned changes, results are inconsistent, even at moderate to high exposure levels.…”
Section: Epidemiology Of Inorganic Arsenic and Cvdmentioning
confidence: 99%
“…These increases were also seen with increasing proportion of urinary monomethylarsonic acid (MMA%), the most toxic arsenic metabolite, and every 10% increase in MMA% was related to an increase of 12.1 μm (95% CI: 0.4, 23.8) in cIMT. More recently, in a cross-sectional study of 199 children 3–14 years of age in México, total urinary arsenic was positively associated with increases in cIMT, with a 35-μm and 58-μm increase in cIMT among children exposed to 35–70 μg/L and > 70 μg/L total urinary arsenic, respectively, compared with those exposed to < 35 μg/L [55]. Although cross-sectional, these data strongly support a role for arsenic exposure in subclinical atherosclerosis, at both high and low-to-moderate levels.…”
Section: Subclinical Atherosclerosismentioning
confidence: 99%
“…A recent study in West Bengal ( n = 91) showed that individuals chronically exposed to arsenic (mean 218 μg/L in well water) had significantly higher MPO activities in serum than the unexposed group, however, no further dose-response relation was found among the exposed group [85]. The only study among children from México found that the proportion of InAs was significantly associated with asymmetric dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide synthase that could lead to endothelial dysfunction and cardiovascular events [55]. However, total arsenic levels were not associated with ADMA.…”
Section: Markers Of Endothelial Dysfunction Inflammation and Oxidatmentioning
confidence: 99%
See 1 more Smart Citation
“…This data is in contrast with the albeit isolated clinical report of Chua et al (14) suggesting an arsenic-related hepatocarcinogenesis effect of the same compound. However, that study bears the main methodological bias in that the authors measured the whole arsenic content, while the literature has clearly demonstrated that only the inorganic component is the one with the noxious effect (28) and the only one deserving monitoring from major epidemiological studies (29,30). On the contrary, the organic one is regarded as safe (31) and its concentration may also vary (32) as probably occurred in their study.…”
Section: Discussionmentioning
confidence: 99%